Maladaptive Eating in Children and Adolescents With Obesity: Scrutinizing Differences in Inhibition - Naets, Tiffany; Vervoort, Leentje; Tanghe, Ann; De Guchtenaere, Ann; Braet, Caroline (Frontiers in Psychiatry, 2020)
Introduction: In order to grasp the complex aetiology of childhood obesity, we aim to clarify the relationship between external eating and weight. Based on theory and empirical evidence, we claim that inhibition is an important moderator in this association. In our first research question we expected that high external eating would be related to a higher weight status, especially for those with high inhibition problems. Secondly, we explored the moderating role of inhibition in the association between external eating and weight change after a multidisciplinary obesity treatment. Method: We investigated n=572 participants (51% boys, aged 7-19) with moderate to extreme obesity recruited in a Belgian inpatient treatment centre. At intake, parents reported on inhibition (BRIEF), while the children and adolescents reported on their eating behaviour (DEBQ). Weight and length were objectively measured pre and post treatment (ADJUSTED BMI). Two hierarchical linear regression models were built to scrutinize the influence of inhibition on the association between external eating and both baseline weight and weight change. Results: First, predicting baseline weight, we found no significant moderating effect of inhibition problems. Second, predicting weight loss, inhibition turned out to be a substantial moderator, specifically in adolescents. Some unexpected gender differences occurred in favour of adolescent boys, in a way that those with high external eating and low inhibition problems lost most weight. Conclusion: Inhibition problems act as a moderator explaining weight loss, but this only holds for adolescents. This suggests that external eating and inhibition play a complex role in weight loss in certain age and gender categories, and stresses the importance of identifying subgroups for tailoring interventions. For those with high inhibition problems, interventions aimed at increasing inhibition skills might be needed to optimize treatment outcomes.